Race in the schoolyard : negotiating the color line in classrooms and communities - Lewis, Amanda E., 1970- (Rutgers series in childhood studies., 2003)
The author draws from her experiences observing classes at three elementary schools, including two multiracial urban, and one white suburban, to reveal how race influences teachers and other school community members in their interactions with each other and their students.